UPAYA PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM KAMPUNG HOME INDUSTRI DI KELURAHAN KARANGANYAR GUNUNG KECAMATAN CANDISARI KOTA SEMARANG - Rahmawati, Nestiar Novika; Widowati, Nina; ., Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
Semarang City's efforts to overcome poverty are by issuing Semarang City Regional Regulation Number 12 of 2016 concerning Poverty Alleviation in Semarang City. One of the innovative efforts made by the Semarang City Government is the establishment of thematic villages. The problems found were lack of use of marketing infrastructure, facilitators shifting responsibilities to each other, poor archivists, lack of active participation and sense of ownership of community programs, lack of facilitator support, community groups not yet integrated, less than optimal income from home industry. This study uses a qualitative method. The technique for determining informants is snowball sampling. Data collection methods through interviews, observation and documentation. The research results show that the socialization stage does not involve an adequate socialization process. In the empowerment process stage, there are obstacles and efforts to resolve problems that have not been carried out. The stage of independence has not been reached because the awareness of taking advantage of opportunities has not been achieved. There are still results and outputs that are not capable of equalizing the welfare of the target community according to the output of Semarang Mayor Regulation Number 22 of 2018 concerning Guidelines for Implementing Thematic Villages. The obstacles found were lack of community participation, limited managerial ability, and lack of ability to manage market opportunities. The advice given is that it is necessary to change the bureaucracy's attitude regarding the nature of empowerment and the nature of its relationship with the target community by changing the perspective of the project and strengthening the potential of the community.